2012
DOI: 10.1111/j.1600-0854.2012.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Multiple Motor Travel via Single Motor Velocity

Abstract: Microtubule-based molecular motors often work in small groups to transport cargos in cells. A key question in understanding transport (and its regulation in vivo) is to identify the sensitivity of multiple-motor-based motion to various single molecule properties. Whereas both single-motor travel distance and microtubule binding rate have been demonstrated to contribute to cargo travel, the role of single-motor velocity is yet to be explored. Here, we recast a previous theoretical study, and make explicit a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
121
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 69 publications
(140 citation statements)
references
References 45 publications
17
121
2
Order By: Relevance
“…As a consequence, the cargo run length now exhibits the opposite behavior as in the case above. Figure 6f shows that the run length is strongly increased for decreasing single motor velocities, as the probability of having both motors bound to the filament increases strongly due to the reduction of the unbinding rate 2 : This is exactly the effect observed by Xu et al 63 with two kinesin motors, who found the run length of two coupled motors to increase when the single motor velocity was decreased.…”
Section: Control Of Travel Distance Through the Velocitysupporting
confidence: 67%
See 4 more Smart Citations
“…As a consequence, the cargo run length now exhibits the opposite behavior as in the case above. Figure 6f shows that the run length is strongly increased for decreasing single motor velocities, as the probability of having both motors bound to the filament increases strongly due to the reduction of the unbinding rate 2 : This is exactly the effect observed by Xu et al 63 with two kinesin motors, who found the run length of two coupled motors to increase when the single motor velocity was decreased.…”
Section: Control Of Travel Distance Through the Velocitysupporting
confidence: 67%
“…independent of the ATP concentration over a rather wide range of ATP concentrations, 59,63 contrary to what one would expect if the ATP concentration only affected the velocity. This observation indicates that a variation of the velocity via the ATP concentration also leads to a variation of the single motor unbinding rate 1 : It can be explained using models for the chemomechanical cycles of kinesin, 46 which also show that this type of dependence is only expected for low concentrations of ADP and inorganic phosphate.…”
Section: Control Of Travel Distance Through the Velocitymentioning
confidence: 47%
See 3 more Smart Citations